9x + 3y = -27

3x + 14y = -48

1 answer

To solve these equations, the most common method is to use the method of substitution. We will solve one equation for one variable and then substitute that expression into the other equation.

Let's solve the first equation for x:

9x + 3y = -27
9x = -3y - 27
x = (-3y - 27)/9
x = (-1/3)y - 3

Now we substitute this expression into the second equation:

3((-1/3)y - 3) + 14y = -48
-1y - 9 + 14y = -48
13y - 9 = -48
13y = -39
y = -3

Now that we have the value for y, we can substitute it back into the first equation to solve for x:

9x + 3(-3) = -27
9x - 9 = -27
9x = -18
x = -2

The solution to the system of equations is x = -2 and y = -3.